2017
DOI: 10.1016/j.polymer.2017.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Disentanglement effects on welding behaviour of polymer melts during the fused-filament-fabrication method for additive manufacturing

Abstract: Although 3D printing has the potential to transform manufacturing processes, the strength of printed parts often does not rival that of traditionally-manufactured parts. The fused-filament fabrication method involves melting a thermoplastic, followed by layer-by-layer extrusion of the molten viscoelastic material to fabricate a three-dimensional object. The strength of the welds between layers is controlled by interdiffusion and entanglement of the melt across the interface. However, diffusion slows down as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
227
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(244 citation statements)
references
References 41 publications
8
227
0
Order By: Relevance
“…In 90° specimens, deposited filaments and their bond interfaces are perpendicular to the load direction. The layer‐to‐layer bond interface often cannot be comparable to bulk materials, since the thermal energy and time provided by the FDM process does not allow for the formation of sufficient diffusion thickness and entanglement at the interface . As a result, 90° specimens tend to facture at those weak bond interfaces (proved by the fracture morphology in Figure S2) and are used as a criteria for the interlayer bond strength of FDM parts .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 90° specimens, deposited filaments and their bond interfaces are perpendicular to the load direction. The layer‐to‐layer bond interface often cannot be comparable to bulk materials, since the thermal energy and time provided by the FDM process does not allow for the formation of sufficient diffusion thickness and entanglement at the interface . As a result, 90° specimens tend to facture at those weak bond interfaces (proved by the fracture morphology in Figure S2) and are used as a criteria for the interlayer bond strength of FDM parts .…”
Section: Resultsmentioning
confidence: 99%
“…When crystalline polymer filaments are used to prepare FDM parts, a square model (length as 100 mm, width as 100 mm, and height as 4 mm, and the width of frames and diagonals is 2 mm) was selected to evaluate the print quality of FDM parts. It is reported that the extrusion process can significantly deform and disentangle the polymer chains as high shear rates of 100–200 rad s −1 was generated in the liquifiers . After deposition, the printed layer cools; meanwhile, the disentangle deformation relaxes via reputation.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamics of confined polymers is an interesting subject that is particularly important for the behavior of nanocomposite materials 1,2 , the phenomenon of surface slip in polymer melts 3,4 , and additive manufacturing 5 . However the dynamics are difficult to characterise and predict.…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with adequate viscosity, polymers should show a sound layer adhesion leading to good weld strength of the manufactured object or piece [7,10,11]. As pointed out by Miegler and coworkers [24], this is related to the capacity of the polymer chains for interlayer diffusion, which is only possible in the terminal or flow viscoelastic region.…”
Section: Cooling and Materials Consolidationmentioning
confidence: 97%
“…Thus, the understanding of the underlying rheological parameters of materials required for a successful printing, which are unclear at the moment and forces manufacturers to a trial-and-error process, can help to expand the number of materials suitable for these manufacturing techniques. Several studies focus on the modelling of melt-extrusion additive manufacturing, both fused filament fabrication [4,7], and extrusion-based printing techniques [8,9]. In essence, 3D printing using polymer melts implies at least three essential features: a) Adequate viscosity to ensure the envisaged printing velocity b) Immediate adhesion of deposed polymer layers and c) Adequate cooling process to guarantee final mechanical properties [10][11][12].…”
mentioning
confidence: 99%